Violence and sexually transmitted infections in pregnancy - Teixeira,Sérgio Araujo Martins (2019)
SUMMARY OBJECTIVE: To synthesize the knowledge produced in studies about the association between violence and STI during pregnancy. METHODS: In this systematic review, we conducted basic activities of identification, compilation, and registration of the trials. The instruments of data collection were studies that investigated, explicitly, relationships between violence, gestation, and STI, from July 2012 to July 2017, using PubMed, Cochrane Library, SciELO, and LILACS. RESULTS: In all, 26 articles were chosen to form the basis of the analysis of this study. The relationship between violence and STI was observed in 22 of the 26 studies, and in eight of them, the violence was practiced during the gestation period. In two studies, there was no evidence of this relationship. In one study, the lack of care for STI was attributed to the unpreparedness of health professionals. Mental disorders were cited as resulting from STI in three articles and in another as a result of violence. One study found more frequent violence against adolescents, while two others cited gestation as a protective factor. CONCLUSIONS: IPV combines characteristics that have a different expression when the woman is in the gestational period. The literature points to a relationship between IPV against women and the presence of STI. The monitoring of pregnancy, whether in the prenatal or postpartum period, offers unique opportunities for the health professional to identify situations of violence and thus provide assistance.